Edutainment experiences for children in retail stores, from a child's perspective. (September 2015) - Feenstra, Florence; Muzellec, Laurent; de Faultrier, Brigitte; Boulay, Jacques
Abstract: To build family traffic in-store and develop spending, retailers offer educational workshops and events targeted at children. Understanding how to create value for children in order to create retail patronage intentions is necessary, but has barely been studied. This papers aims to explore the nature and benefits of these edutainment experiences for children and their potential effects on the child-retailer relationship through ethnographic investigation. The study provides evidence that children enjoy acquiring consumer knowledge and consumer attitudes autonomously by taking on an active role as consumers. Edutainment experiences endorse a positive vision of "fun power", as a new type of child influence on adult purchasing. They determine long-term orientation in child-retailer relationships. Highlights: In-store edutainment experiences serve the children's well-being and pleasure These experiences are both key agents of socialization and reverse socialization They modify the nature of children's influence on family's purchasing process in-store A positive fun power vision appears in a win-win perspective of shopping experience These experiences are a way to develop long term child-retailer relationship